IMPLEMENTING THE TIKRAR METHOD TO ENHANCE THE COGNITIVE CAPACITY OF CHILDREN WITH SPECIAL NEEDS IN INCLUSIVE TAHFIZ EDUCATION - Triana, Rumba; Zakaria, Aceng; Suretno, Sujian (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: This study aims to examine the implementation of the Tikrar method as a strategy to enhance the cognitive capacity of children with special needs (CWSN) in tahfiz learning at the Al-Wildan Bekasi Inclusive Tahfiz School. Method: The research uses a Participatory Action Research (PAR) approach, involving researchers, tahfiz teachers, inclusion teachers, parents, and student facilitators through cycles of planning, action, observation, and reflection. Data was collected through structured observations, in-depth interviews, documentation, and pre- and post-tests of memorization. Result: The results show significant improvements in working memory, concentration, verse repetition ability, reading accuracy, and overall student engagement. The average memorization improvement ranged from 37% to 83%, with notable progress among students with attention deficits and mild learning disabilities. The study concludes that Tikrar not only serves as an effective memorization method but also enhances cognitive structures, emotional regulation, and behavioral stability in CWSN. The method proves to be a highly relevant pedagogical approach for inclusion-based tahfiz education, provided it is adapted to the individual needs of each student. Conclusion: The findings suggest integrating Tikrar into the inclusive tahfiz curriculum as an effective tool for improving both cognitive and emotional development. Suggestion: Further research is recommended to explore the long-term effects of Tikrar and its adaptation in digital formats to increase engagement and motivation among students with special needs.